2016
DOI: 10.1097/ajp.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Triggers as a Possible Source of Pain in a Subgroup of Tension-type Headache Patients?

Abstract: Understanding the possible triggers in TTH, muscle hyperalgesia, and widespread pain sensitization, may help to develop better management regimes and possibly prevent TTH from developing into more chronic conditions. Currently, there is a striking difference between the clinical observational studies favoring the role of muscle triggers in TTH and the intervention studies generally not supporting the role of muscle triggers in TTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 90 publications
(113 reference statements)
1
16
0
1
Order By: Relevance
“…This raises the question whether neck tenderness is an indicator for distinct subtypes of migraine: patients with neck pain as a simple symptom prior or during the attack without any identifiable changes in the periphery, and patients where the neck plays a crucial role either as a trigger or as a perpetuator for migraine attacks. The second group, if untreated, could be susceptible to ongoing nociceptive input from the neck, which activates the trigeminocervical system and subsequently leads to more frequent headache attacks, eventually contributing to the transition from episodic to chronic headache [ 16 , 17 ]. Although these statements were originally related to tension-type headache, considering the partially related pathobiology, this might also be true for migraine.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question whether neck tenderness is an indicator for distinct subtypes of migraine: patients with neck pain as a simple symptom prior or during the attack without any identifiable changes in the periphery, and patients where the neck plays a crucial role either as a trigger or as a perpetuator for migraine attacks. The second group, if untreated, could be susceptible to ongoing nociceptive input from the neck, which activates the trigeminocervical system and subsequently leads to more frequent headache attacks, eventually contributing to the transition from episodic to chronic headache [ 16 , 17 ]. Although these statements were originally related to tension-type headache, considering the partially related pathobiology, this might also be true for migraine.…”
Section: Discussionmentioning
confidence: 99%
“…Active TrPs are those provoking spontaneous symptoms and the elicited referred pain reproduces the symptom experienced by the patient [1]. It has been reported that active TrPs reproduce the symptoms experienced by individuals experiencing mechanical neck pain [2], lateral epicondylitis [3], PM R 9 (2017) [1208][1209][1210][1211][1212][1213][1214][1215][1216] www.pmrjournal.org whiplash [4], tension-type headache [5,6], fibromyalgia [7,8], temporomandibular pain [9], or shoulder pain [10,11]. Several therapeutic approaches are proposed for the management of myofascial pain including the growing trend of TrP dry needling (TrP-DN) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Current research into the pathogenesis of TTH focuses on the role of muscle tissues (Arendt-Nielsen et al, 2016) and facilitation of nociceptive pain processing (de Tommaso and Fern andez-de-las-Peñas, 2016). It has been argued that TTH has a muscle component (Bendtsen and Fern andez-de-las-Peñas, 2011) and that sensitization processes play an important role in the transition from acute to chronic TTH (Yu and Han, 2015).…”
Section: Introductionmentioning
confidence: 99%